2008
DOI: 10.1007/s11606-008-0521-4
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in the VA Health Care System: A Systematic Review

Abstract: Existing evidence from the VA indicates several promising targets for interventions to reduce racial disparities in the quality of health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
192
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(199 citation statements)
references
References 65 publications
(33 reference statements)
3
192
4
Order By: Relevance
“…Previous studies have systematically reviewed aspects of care at the VA. [5][6][7] Two peer-reviewed articles based on one of these 7 summarized the available evidence on medical 8 and surgical 9 care quality through 2009. This review indicated that in most studies, the care provided in the VA compares favorably to non-VA systems.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have systematically reviewed aspects of care at the VA. [5][6][7] Two peer-reviewed articles based on one of these 7 summarized the available evidence on medical 8 and surgical 9 care quality through 2009. This review indicated that in most studies, the care provided in the VA compares favorably to non-VA systems.…”
Section: Introductionmentioning
confidence: 99%
“…26 Because quality improvement has been associated with reductions in disparities, 27,28 it is plausible that racial disparities in adherence to CRCS could be nonexistent in the VHA. On the other hand, racial disparities in CRCS adherence could exist within the VHA, because racial disparities in care continue to exist in this setting across a broad range of clinical areas and types of services 29 and because Black patients may have fewer cognitive and environmental resources that contribute to adherence. Existing VA studies provide conflicting evidence about the presence of racial disparities in CRCS, and have significant limitations.…”
mentioning
confidence: 99%
“…[2][3][4][5] In this editorial, we will attempt to synthesize the results of these studies and make recommendations on how to shape future research to reduce, but preferably to completely eliminate, healthcare disparities. These recommendations should be useful to clinicians, researchers, administrations, and policy makers.…”
mentioning
confidence: 99%
“…The manuscript by Saha et al 2 reviews the disparity literature in the VA-the largest healthcare provider in the USA. The VA in many ways is an ideal 'laboratory' for exploring disparities because access to health care, which is an important cause of health care disparities, is not an issue, and access to affordable medications, a huge barrier in other settings, is of minimal concern.…”
mentioning
confidence: 99%
See 1 more Smart Citation